Pelatihan Membaca Dan Menghafal Surat Pendek Secara Tartil Untuk Meningkatakan Prestasi Belajar Santri TPQ Raudlotul Qur’an Senowo Kencong Di Masa Pandemi - Faridhatul Khasanah; Haryadi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
One of the etiquette of reading the Qur'an is to read the Qur'an with tartil, as the word of Allah SWT "and read the Qur'an with tartil", (QS. Al-Qiyamah 17-18) Reading the Qur'an -The Qur'an certainly has many virtues. Starting from being our intercessor on the last day, getting rewards, to blessings for us in living life in this world. And of course, reading the Qur'an and its tartil will bring more virtue to us. In accordance with this background, the general objective of this training is to contribute to the community regarding the importance of inculcating good religious skills, and strengthening religious beliefs for the children themselves. In this study, the author uses and chooses the PAR (Participatory Action Research) method, basically PAR is a research that involves all relevant parties in actively researching the current action together in order to change and improve it. PAR is participatory in the sense that it is a necessary condition that people play a key role in it and have relevant information about the social system (community) under study, and that they participate in the design and implementation of the action plan based on the results of the research. Community service activities, especially at TPQ Raudlotul Qur'an Senowo Kencong, can run well, this can be seen from: students can learn how to pronounce makhorijul letters properly and correctly, and students seem to have mastered the makhorijul letters that have been studied. The success of this program cannot be separated from the support from the community, good communication and cooperation with the community around TPQ.